Microbial Diversity of Genital Ulcers of HSV-2 Seropositive Women. Issue 1 (December 2017) - Mehta, Supriya; Pradhan, Ashish; Green, Stefan; Naqib, Ankur; Odoyo-June, Elijah; Gaydos, Charlotte; Barry, Sheila; Landay, Alan; Bailey, Robert
Abstract We measured the microbial community structure of genital ulcers in women. Swabs from clinically detected ulcers were tested for HSV-2 andTreponema pallidum by polymerase chain reaction (PCR). HSV-2 andT .pallidum were detected by serum antibody testing. Microbial community structure was characterized by high-throughput 16 s rRNA gene amplicon sequencing. Multiple group testing and Elastic net and Lasso regressions identified taxa associated with differences in factors of interest. Among 49 ulcer specimens from 49 HSV-2 seropositive women, by PCR HSV-2 was recovered from 28 (57%) specimens andT .pallidum from none; one woman showed serologic evidence of syphilis. Overall, 63% of women were HIV-positive and 49% had an uncircumcised male sex partner. By both multiple group testing and regression, Porphyromonas (FDR p-value = 0.02), Prevotella (FDR p-value = 0.03), Anaerococcus (FDR p-value = 0.07), andDialister (FDR p-value = 0.09) were detected at higher relative abundance in HSV-2 PCR-positive than negative ulcers. The presence of HSV-2 in a lesion was associated with presumed bacterial agents of Bacterial vaginosis. Differences in bacterial communities may contribute to HSV-2 ulcer pathogenesis, severity, or prolonged healing. If these results are confirmed, future studies may consider the influence of BV treatment on women's GUD and HSV-2 incidence and recurrence.